Pirate king [large type] : a novel of suspense featuring Mary Russell and Sherlock Holmes - King, Laurie R. (King, Laurie R. Mary Russell novel., 2011)
In England<U+2019>s young silent-film industry, the megalomaniacal Randolph Fflytte is king. But rumors of criminal activities swirl around his popular movie studio. At the request of Scotland Yard, Mary Russell travels undercover to the set of Fflytte<U+2019>s latest cinematic extravaganza, Pirate King. Based on Gilbert and Sullivan<U+2019>s The Pirates of Penzance, the project will either set the standard for moviemaking for a generation . . . or sink a boatload of careers. As the company starts rehearsals in Lisbon, the thirteen blond-haired, blue-eyed actresses whom Mary is chaperoning meet the swarm of real buccaneers Fflytte has recruited to provide authenticity. But when the crew embarks for Morocco and the actual filming, Russell senses ominous currents of trouble: a derelict boat, a film crew with many secrets, decks awash with budding romance<U+2014>and now the pirates are ignoring Fflytte and answering only to their outlaw leader. Where can Sherlock Holmes be? As movie make-believe becomes true terror, Russell and Holmes themselves may experience a final fadeout.